THE IMPACT OF ASSET MANAGEMENT, CAPITAL STRUCTURE, AND FIRM SIZE TOWARD PROFITABILITY - Priskila , Priskila; Dewi, Sofia Prima (International Journal of Application on Economics and Business, 2023)
The aim of this study is to determine the influence of asset management, capital structure, and company size on the profitability of non-cyclical sector manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period. The data population in this study amounted to 111 non-cyclical sector manufacturing companies, a non-probability sampling technique (purposive sampling) by applying several criteria in this study. The data sample used is 75 data with 25 companies in the 2018-2022 period, where later the data will be processed using E-views ver.12 software. In this study, a classical assumption test was carried out using the multiple linear regression method and the suitable result for this study was the Random Effect Model (REM). This research shows that asset management has a positive effect on profitability, capital structure negatively affects profitability, and the size of the company has no impact on profitability with negative direction.